2021
DOI: 10.1016/j.arth.2020.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Resuming Elective Surgery During the COVID-19 Pandemic

Abstract: Background Many U.S. health systems are grappling with how to safely resume elective surgery amid the COVID-19 pandemic. We used online crowdsourcing to explore public perceptions and concerns toward resuming elective surgery during the pandemic, and to determine factors associated with the preferred timing of surgery after health systems reopen. Methods A 21-question survey was completed by 722 members of the public using Amazon Mechanical Turk. Multivariable logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 36 publications
4
43
0
11
Order By: Relevance
“…The capacity of beds was tested during the year, and the American College of Surgeons guidelines suggested that lower acuity surgery could be performed at ambulatory surgical centres. 10 As other institutions attempted to restart elective work 11 , 12 fears of public perception 13 and protocol to limit the risk of spread have been at the forefront. 14 …”
Section: Introductionmentioning
confidence: 99%
“…The capacity of beds was tested during the year, and the American College of Surgeons guidelines suggested that lower acuity surgery could be performed at ambulatory surgical centres. 10 As other institutions attempted to restart elective work 11 , 12 fears of public perception 13 and protocol to limit the risk of spread have been at the forefront. 14 …”
Section: Introductionmentioning
confidence: 99%
“…In December 2019, the first case of a novel coronavirus, named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was reported in Wuhan, China [1]. The disease caused by SARS-CoV-2 was later named coronavirus disease 2019 (COVID- 19), and on March 11, 2020, WHO declared COVID-19 a pandemic [2]. The first US cases were reported in Seattle, Washington in February, 2020, followed shortly by cases in New York, which quickly became the primary epicenter of the outbreak in the United States [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in other specialties have explored the patient perspective on resuming elective procedures during the pandemic, with mixed results. 12 , 13 , 14 , 15 There are also several orthopedic-specific studies that have examined patient perspectives, with most of them focusing on total joint arthroplasty. 16 , 17 , 18 , 19 These studies have shown varying impacts on patient well-being, progression of disease, and anxiety surrounding elective procedures in the COVID-19 era.…”
mentioning
confidence: 99%